Exemptions, Sincerity and Pastafarianism. Issue 2 (28th August 2019) - Martin, Nick
ABSTRACT: Because Pastafarianism – or the Church of the Flying Spaghetti Monster – is a parodic religion, common sense suggests its 'adherents' should not receive exemptions. However, the prima facie case for excluding Pastafarians is complicated by the fact that many assert their religion is as legitimate as any other religion and that their beliefs are genuine. Indeed, Pastafarians have already obtained exemptions in various countries. Taking the dominant liberal egalitarian, integrity‐based approach to exemptions, this article investigates whether there is a principled, objective basis for excluding Pastafarians that accounts for their assertions. To that end, I examine four tests: a religion, seriousness, obligation, and sincerity test . I assess whether each test can actually exclude Pastafarians, and if it could, can it do so in a way that is consistent with liberal egalitarian commitments. I argue that only a sincerity test – based on consistent behaviour and a willingness to bear the costs of one's beliefs – satisfies both of these conditions, but, on a weak and contingent basis.